2013
DOI: 10.14250/cement.67.165
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Length Change of Cementitious Material Based on Quaternary System

Abstract: KEY WORDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, this system is very sensitive to temperature, mix proportions, and the quality of raw material. We previously reported that difference in compressive strength could not be due to the difference in porosity and gel space ratio; therefore, it was important to consider different kinds of hydrate and their volumes (Mori et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, this system is very sensitive to temperature, mix proportions, and the quality of raw material. We previously reported that difference in compressive strength could not be due to the difference in porosity and gel space ratio; therefore, it was important to consider different kinds of hydrate and their volumes (Mori et al 2015).…”
Section: Introductionmentioning
confidence: 99%